2006
DOI: 10.1158/0008-5472.can-05-2741
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersal of Replication Proteins after Etoposide Treatment Requires the Cooperation of Nbs1 with the Ataxia Telangiectasia Rad3-Related/Chk1 Pathway

Abstract: In mammalian cells, DNA replication takes place in functional subnuclear compartments, called replication factories, where replicative factors accumulate. The distribution pattern of replication factories is diagnostic of the different moments (early, mid, and late) of the S phase. This dynamic organization is affected by different agents that induce cell cycle checkpoint activation via DNA damage or stalling of replication forks. Here, we explore the cell response to etoposide, an anticancer drug belonging to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Beside its well-known effects on G 2 -M phase of the cell cycle, etoposide has been shown to have an inhibitory mechanism also on S-phase progression, retaining cells in the latter half of the S phase (32,33). Accordingly, our data showed that etoposide (5 Amol/L) induced an accumulation of cells in both S phase (47%) and G 2 -M phase (35%).…”
Section: Perifosine Increases the Apoptotic Rate In Cells Committed Tsupporting
confidence: 51%
“…Beside its well-known effects on G 2 -M phase of the cell cycle, etoposide has been shown to have an inhibitory mechanism also on S-phase progression, retaining cells in the latter half of the S phase (32,33). Accordingly, our data showed that etoposide (5 Amol/L) induced an accumulation of cells in both S phase (47%) and G 2 -M phase (35%).…”
Section: Perifosine Increases the Apoptotic Rate In Cells Committed Tsupporting
confidence: 51%
“…The topoisomerase II inhibitor etoposide provokes DSBs, as well as the rapid activation of ATM, ATR, DNA-PK and their corresponding substrates. [24][25][26] Exposing E14.5 retinas to etoposide in organotypic culture increased the accumulation of gH2AX and total p53 (Figure 3a), two common substrates of ATM, ATR and DNA-PK, 13,14,16 and indicative of the response of retinal cells to a genotoxic agent. Chk1, which is primarily activated by ATR, 16,27 also seemed to be phosphorylated in etoposide-treated retinas.…”
Section: Resultsmentioning
confidence: 99%
“…22 We have previously shown that bleomycin does not affect the association of replicative enzymes with replication factories. 23 Co-staining with α-LigI and α-Nbs1 antibodies demonstrate that after belomycin treatment Nbs1 and LigI colocalize at replication factories (Fig. 4D, Part a).…”
Section: Resultsmentioning
confidence: 91%